Identity exploration of university students in the somatic and material domains: the mediating role of conspicuous consumption - Adebo, Adetumilara Iyanuoluwa; Hamsan, Hanina Halimatusaadiah (Arabian Gulf University, 2023)
This paper is determined to examine the role of body image and materialism in predicting the identity exploration of university students when conspicuous consumption is a mediator variable.The study used a quantitative method. Data were collected from students of three federal universities in Nigeria. The sample size was 331. A self-report questionnaire was used to collect data and analysis was performed using the partial least squares structural equation modelling.Findings reveal that materialism has a negative association in predicting the identity exploration of students. At the same time, there was a significant full and partial mediating effect of conspicuous consumption on the relationship between body image and materialism on identity exploration, respectively.The study provides valuable information for parents in understanding how conspicuous consumption may influence their children’s identity formation. The findings can also be helpful for educators in the design of discussions and interventions for students on the social-psychological antecedents of conspicuous consumption and identity exploration. Government and regulatory agencies can use the study’s findings to shape student financial literacy and consumer protection policies.This study makes both theoretical and methodological contributions to the existing literature. It provided concrete empirical evidence establishing a subtle connection between the symbolic self-completion theory and the identity status paradigm. It is also amongst the first single research conducted within the scope of these two theories in the Nigerian higher education context.